Memacu Peningkatan Kualitas Pribadi untuk Meningkatkan Kualitas Institusi (Telaah Manajemen Sumber Daya Manusia di MI Al Illahiyah Rejoagung Ngoro Jombang) - Achmad Anwar Abidin (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2016)
process of producing the expected personal qualities, is certainly necessary effort is not easy and the sacrifice that is not cheap. Here is an institution that houses must be capable of being the support and encouragement to spur an increase in the personal qualities of the employees both educators and its educational staff because essentially that's the institution itself that will harvest the quality of the individuals. MI Al Illahiyah are educational institutions at the elementary level (elementary school) located in Redjoagoeng village Ngoro - Jombang district that has stood for a long time and belong to the old school were less significant development even stagnant from year to year. Therefore, it is necessary to undertake actions that can upgrade quality of the institutions in order to grow significantly. Personal qualities or quality of each individual human being is different to find, analyze and then needed of increasing human resource management (HRM) is good and accurate. Human resource management is a process of planning, organizing, directing and controlling the procurement of energy, development, compensation, integration, maintenance, and termination of employment with the human resources to achieve the goals of individuals, organizations working, institutions, and communities. The main purpose of human resource management is to increase the contribution of its human resources to the organization or institution in order to achieve the goals of the organization or institution in question The Supporting faktors and inhibitors a personal quality improvement is : a. Leadership b. Regulatory rules c. Reward and Punishment and d. Personal motivation. Then The things that must be done to improve the Personal Quality is: a. Following courses and training. b. Discussion subjects teacher (Teacher Meeting) c. Questionnaire feedback from students d. Recording a learning process that has been done. e. Conducting Study Tour. To improve the personal qualities of an institution should at least be able to do things as follows : Motivating , Acknowledge individual , Giving Opportunities for positive activities for self-development . Periodically conduct training , conduct Job Performance Assessment (Performance appraisal ) , Gives Compensation , and Creating Effective Working Relationships.